Merkel Cell Polyomavirus Small T Antigen mRNA Level Is Increased following In Vivo UV-Radiation - Mogha, Ariane (Public Library of Science, 2010)
Merkel cell carcinoma (MCC) is a rare but aggressive skin cancer involving Merkel cells. Recently, a new human polyomavirus was implicated in MCC, being present in 80% of the samples analyzed. In virus-positive MCC, the Merkel cell polyomavirus (MCPyV) is clonally integrated into the patients DNA, and carries mutations in its large T antigen, leading to a truncated protein. In non-symptomatic tissue MCPyV can reside at very low levels. MCC is also associated with older age, immunosuppression and sun exposure. However, the link with solar exposure remains unknown, as the precise mechanism and steps involved between time of infection by MCPyV and the development of MCC. We thus investigated the potential impact of solar simulated radiation (SSR) on MCPyV transcriptional activity. We screened skin samples of 20 healthy patients enrolled in a photodermatological protocol based on in vivo-administered 2 and 4 J/cm(2) SSR. Two patients were infected with two new variants of MCPyV, present in their episomal form and RT-QPCR analyses on SSR-irradiated skin samples showed a specific and unique dose-dependent increase of MCPyV small t antigen transcript. A luciferase based in vitro assay confirmed that small t promoter is indeed UV-inducible. These findings demonstrate that solar radiation has an impact on MCPyV mRNA levels that may explain the association between MCC and solar exposure.